2009
DOI: 10.5009/gnl.2009.3.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Food Residue after Distal Gastrectomy and a New Effective Preparation for Endoscopy: The Water-Intake Method

Abstract: Background/AimsFood residue is frequently observed in the gastric remnant after distal gastrectomy, despite adequate preparation. We devised a water-intake method to reduce food residue in the gastric remnant by drinking large quantities of water in a short time. The aims of this study were to identify the risk factors for food residue and to study the effectiveness of this new method for endoscopy preparation.MethodsA cohort of 708 patients who underwent distal gastrectomy for gastric cancer was reviewed pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Unfortunately, we failed to determine the risk factors for the food residue. To decrease the incidence, fasting more than 18 h before the examination [11], drinking water on the evening before and on the day of the endoscopy [10,17], and ingesting only a liquid or soft diet on the day before the examination [11] have been recommended for gastrectomized patients to reduce the food residue in their gastric remnant. These preparation methods can also be applied for esophagectomized patients to minimize the presence of food residue from their gastric pull-ups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, we failed to determine the risk factors for the food residue. To decrease the incidence, fasting more than 18 h before the examination [11], drinking water on the evening before and on the day of the endoscopy [10,17], and ingesting only a liquid or soft diet on the day before the examination [11] have been recommended for gastrectomized patients to reduce the food residue in their gastric remnant. These preparation methods can also be applied for esophagectomized patients to minimize the presence of food residue from their gastric pull-ups.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason is that the present study only evaluated the first endoscopic images, even if the patient had undergone multiple endoscopies at our center. Repeated examinations probably reduce the food residue from the gastric pull-up because the patients try to prepare more carefully than in their previous failed examinations [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to date, there is limited data regarding the effects of different preparation regimens for endoscopy in postgastrectomy patients. One recent study showed that the intake of a large quantity of water (1L) in a short time was effective and convenient for endoscopy preparation in patients who presented food residue [6] . However, ingesting a large volume of water is not well tolerated by the patients.…”
Section: Introductionmentioning
confidence: 99%